Incidence of оbesity among students - Antonić, Roland; Ilić Udovičić, Dragana; Vasić, Aleksandra; Damnjanović, Danijela; Popović, Kosana; Jevtić, Ivana (Archives of Pharmacy, 2022)
Obesity is a risk factor for many health disorders and is becoming an increasing health problem in the student population. This study aimed to investigate the prevalence of obesity in the student population and the presence of sleep disorders as risk factors for obesity. The examination was conducted during the 2018/2019 year at the Department of Medical and Business-Technological Studies in Sabac. The examined group consisted of 173 students an average age of 22,87±1,68 years. The examinees were given their body mass index and waist circumference, and a questionnaire was used to evaluate their habits. According to the body mass index, 28,57% of the students were already overweight in the first year of study, whereas 10,20% were obese. In the second year of study, 22,92% of the students were overweight, while in the third year of study, the lowest percentage of overweight was 14,47%, and 2,63% obese. The average sleep duration during the day of students was 7,87±0,63 hours, and the presence of sleep disorders was not recorded. A higher incidence of obesity and adiposity was found in male examinees. High-risk waist circumference values were found in 9,20% of male respondents. Obesity was with the highest prevalence in students of the Gastronomy study program. The results show that students need to be educated about obesity and timely diagnosed and treated.